Scanning electron microscopic studies on the effects of Xiang Sha Yang Wei Wan on ethanol-induced gastric ulcer in the rats - Al-Ani, Imad Matloub Dally; Saliem, Ahmed Muhammed; Abdel Wahab, Emad Mohamad Nafie; Faisal, Ghasak Ghazi (Microscopy Society (Singapore), 2018)
Objective: The purpose of the present study was to investigate the gastro-protective potential of Xiang Sha Yang Wei Wan (XSYWW) against lesions in gastric mucosa layers induced by ethanol in experimental rats using scanning electron microscopy (SEM). Methods: Thirty healthy male Sprague-Dawley rats (250-300 gm) were divided into three groups. Group I (control group); gastric ulcers were induced by administering 100% ethanol (1 ml/200 g). Group II (Pre-treatment group) was divided into two subgroups; they were orally fed with 1.0 gm/kg and 2.0 gm/kg respectively of XSYWW solution. Thirty minutes later they were administered with absolute ethanol as in group I. Group III, (post-treatment group) was given an oral dose of 2gm/kg of XSYWW solution after one hour of ethanol administration. Five rats from groups I, and III were sacrificed on day 1, 2 and 3 while the animals of group II were sacrificed one hour after ethanol administration. Results: SEM study of the surface of the gastric mucosa from group I showed multiple ulcers of packed swollen cells and appearance of underlying connective tissue. The gastric mucosa of group II rats showed less severity ulcers with the formation of flattened, mesh like structures in the mucosal epithelium; while those of group III showed signs of improvement and regeneration of the mucosal surface. Conclusion: Pre- or post-treated rats with XSYWW revealed a protective effect against ethanol-induced gastric mucosal lesion.